Ca2+ - substitution effect on the electronic structure of CaCu3Ti4O12 studied by electron spectroscopy for chemical analysis. Issue 4 (15th February 2021) - Jani, Komal K.; Barad, Divyesh V.; Raval, Pooja Y.; Nehra, Monika; Vasoya, Nimish H.; Jakhar, Narendra; Modi, Kunal B.; Kumar, Sandeep; Lim, Dong-Kwon; Singhal, Rishi Kumar
Abstract: A detailed electronic structure study of quadruple perovskite series, Ca1+ x Cu3- x Ti4 O12 (for x  = 0.0, 0.1, 0.2, 0.5, 1.0), using electron spectroscopy for chemical analysis (ESCA) has been carriedout. The Ti2 p ESCA spectra imply that Ti ions remain in the tetravalent state and show the presence of Ti clusters, TiO6 and TiO5 . The Cu2 p spectra indicate the dominance of the divalent state of Cu ions. The Ca2 p spectra show that Ca atoms are divalent but spectral features are suggestive of the presence of Ca superficial atoms in the system which is possibly due to the precipitation of Ca atoms in the grain boundary regions. The Ca 2p in conjunction with O1 s spectra shows that there is a strong possibility of hybridization of Ca2 p states with the O1 s and/or the Cu 3d orbitals. The remarkable shift in O1 s spectra towards the lower energy side for the samples with x  ≥ 0.5 is mainly due to the substitution of large cation Ca 2+ (1.0 Å), for small cation Cu 2+ (0.73 Å) in the series. That results in bond length enhancement and weakening of the bond strength. It is proposed that the shift of O1 s peaks can also be partially caused by oxygen vacancies; nevertheless, more experiments are required to substantiate this.